Public Health perspectives on Cryptocurrency: The Good, The Bad and The Ugly - Ramanathan, Vanisree; Tripathi, Shailesh; Bhattacharya, Sudip; Varshney, Saurabh (Indian Journal of Community Health, 2023)
Digital currencies like bitcoin utilize encryption to secure financial transactions, verify their legitimacy, and limit supply. Because there is no central authority over it, like a government or bank, we say that it is decentralized. Instead, cryptocurrency transactions are recorded on a public digital ledger called a blockchain, which serves as a decentralized database that records all transactions made with the currency.(1) The use of cryptography ensures that the transactions are secure and anonymous, making it difficult to counterfeit or double-spend the currency. On online exchanges, cryptocurrencies can be purchased and traded, and they can also be used to purchase products and services online.(2) There are risks and hurdles associated with cryptocurrencies, including as their volatility, regulatory ambiguity, and security concerns, even though they have the potential to revolutionize the way we think about money and banking. As with any investment or financial decision, it is important to do your research and consult with experts before investing in cryptocurrencies. There are many different types of cryptocurrencies, with new ones being created regularly.(1) Here are some of the most common types: